2022
DOI: 10.3389/fpsyg.2022.1018601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exergames on mood and cognition in healthy older adults: A randomized pilot study

Abstract: The elderly population is increasing and the implementation of stimulating training to promote active aging has become a research issue. This study aimed at investigating the effects of a cognitive-motor exergame training on cognitive functions and mood, in healthy older adults. A randomized controlled pilot study was conducted to compare a cognitive-motor exergame training with a passive control group. The training consisted of 8 sessions of 45 min each, including 10 interactive activities focused on several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Exergames, also known as exercise games, are interactive technology-based physical activities that are designed to provide an enjoyable and engaging way to get physically active (Sween et al, 2014). Exergames have gained popularity in recent years, particularly among older adults or individuals with chronic conditions, as a way to promote physical activity and improve physical fitness (Sween et al, 2014;Moret et al, 2022). Exergames can involve a wide range of physical activities, from dancing and jumping to moving arms and using other body movements to control the game (Asín-Prieto et al, 2020;Lopes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exergames, also known as exercise games, are interactive technology-based physical activities that are designed to provide an enjoyable and engaging way to get physically active (Sween et al, 2014). Exergames have gained popularity in recent years, particularly among older adults or individuals with chronic conditions, as a way to promote physical activity and improve physical fitness (Sween et al, 2014;Moret et al, 2022). Exergames can involve a wide range of physical activities, from dancing and jumping to moving arms and using other body movements to control the game (Asín-Prieto et al, 2020;Lopes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Exergames can involve a wide range of physical activities, from dancing and jumping to moving arms and using other body movements to control the game (Asín-Prieto et al, 2020;Lopes et al, 2020). Research has shown that regular participation in exergames can improve coordination, balance, and other physical fitness measures, as well as reduce stress and improve mental health outcomes such as mood and cognitive function (Sween et al, 2014;Moret et al, 2022). Exergames can be played on video game consoles, smartphones, and VR head-mounted displays, and are suitable for people of all ages and fitness levels (Asín-Prieto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in cognitive outcomes between active breaks outside and those with games may be obscured by this individual variability. Moreover, an investigation of the long-term or chronic effects of active breaks might be required to detect meaningful differences between the two interventions as this study was predicated on the acute effects of outdoor breaks and exergames on attention [ 91 ]. These neurophysiological considerations make it clear that the lack of differences in some of the tested cognitive parameters between active outdoor breaks and exergames among carers may be due to the acute effects of physical activity on attentional processes and overlapping neural mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, this type of game can encourage physical activity, which is particularly important for older people, who may face some physical limitations, especially in mobility and balance, which can have positive implications for mental health [9]. Additionally, exergames can also be beneficial in promoting cognition in older adults, including memory, attention, and reasoning [10]. This type of game helps to reduce the possibility of experiencing loneliness and social isolation, as in this type of game, older adults interact with other people, which is positive for their mental health [11].…”
Section: Introductionmentioning
confidence: 99%